Sodobni slovenski roman na gledališkem odru - Marušič, Breda (Slavistična revija, 2014)
The Contemporary Slovene novel, in comparison to Slovene realist classics and to foreign novelistic texts, relatively rarely appears on theater stages. Its dramatization is most common as a part of dramatic theater, although novels with predominantly modernistic features are often used as a basis for post-dramatic theater forms (they both reject the plot). The form of dramatization depends more on the type of the dramatist (author or director) than on the type and features of the novel itself. Various elements of drama and possibility of performance may make a novel more attractive for adaptation, but they are not sufficient for a quality dramatization or performance. A dramatic text created in the process of dramatization is, as any other dramatic text, only a starting point for various directorial readings.
Keywords: "Čefurji raus!"; "Filio ni doma"; "Katarina, pav in jezuit"; Bojetu, Berta, 1946-1997; contemporary Slovene novel; dramatizacija; dramatization; Jančar, Drago, 1948-; Slovene literature; Slovenian theatre; slovenska književnost; slovenski roman; slovensko gledališče; Vojnović, Goran, 1980-